PP259 Invisible Resilience: The Value Of Medical Technology In Reducing Population And Health Systems' Vulnerability To COVID-19. (December 2021) - Steuten, Lotte; Zamora, Bernarda; Lothgren, Mickael; Bruce, Andrew; Towse, Adrian
Abstract : Introduction: COVID-19 has exposed population and health systems' vulnerability to a highly infectious disease. People with diabetes have a higher risk of COVID-19 hospitalization and death than those without. Medicines that control blood glucose reduce this risk. We quantified COVID-19 hospital admissions and deaths averted by diabetes medicines in the UK during the March-May 2020 wave. Methods: We estimated COVID-19 hospital and intensive care unit (ICU) admissions averted and COVID-19 hospital deaths avoided by diabetes medicines, considering a counterfactual where those medicines were not available. We used published UK-data sources on diabetes prevalence, proportion of patients achieving diabetes control with medicines, COVID-19 infection risk, probabilities for COVID-19 hospital admission, subsequent ICU admission and hospital death. We calculated the relative risk reduction of controlled vs. uncontrolled diabetes on COVID-19 hospital or ICU admission (71% and 66%, respectively), and hospital death (38%) from the UK Open Safely data. Results: Diabetes medicines are estimated to have averted 17, 417 hospital admissions, 2, 752 ICU-admissions and 438 hospital deaths due to COVID-19 compared to a counterfactual where those medicines had not been available in the UK. Conclusions: Effective medicines to control diabetes contribute to population and health systems resilience against COVID-19. Health technology assessment and policy makers should recognize that adoption and usage of health technology reduces societies' vulnerability to similar shocks.